Information and communication technology-based learning practices and teacher professional development - Suardi, Suardi; Faridah, Faridah; Sultan, Sultan; Herman, Herman (International Journal of Evaluation and Research in Education (IJERE), 2025)
The rapid development of information technology has implications for its massive use in the field of education. Expectations for teachers to integrate technology into their learning practices and professional development are increasing. The teacher’s ability to integrate technology in these two activities is influenced by various factors. However, previous research has not focused on uncovering how gender, experience, certification status, and social media can contribute to information and communication technology (ICT)-based learning practices and professional competency development for teachers. Based on this gap, this research was designed to investigate the contribution of gender, experience, certification status, and social media access to teachers’ ICT-based learning practices and professional competency development. The current research was designed as a cross-sectional survey. A total of 1,756 elementary school teachers in South Sulawesi, Indonesia, were involved as research samples through online questionnaire data collection. The research results showed that there were differences in teachers’ learning practices and professional development intentions based on work experience and intensity of social media access. However, no differences were found in gender variables and certification status. Thus, these two variables become key elements in integrating ICT in learning in the future. These findings will be beneficial for teacher training institutions and policy makers.